Religion and sexuality in American literature - Morey, Ann-Janine (Cambridge studies in American literature and culture, 1992)
Although sometimes religion and sexuality are treated as an aberrant theme in American literary and religious history, American writers from Nathaniel Hawthorne to John Updike have been fascinated with the connection between religious and sexual experience. Through the voice of American fiction, Religion and Sexuality in American Literature examines the relations of body and spirit (religion and sexuality). Using both canonical and non-canonical fiction, Ann-Janine Morey examines novels dealing with the ministry as the medium wherein so many of the tensions of religion and sexuality are dramatised and then moves to contemporary novels that deal with moral and religious issues through metaphor. Based upon a sophisticated and selective application of metaphor theory, deconstruction and feminist postmodernism, Morey argues that while American fiction has replicated many traditional animosities, there are also some rather surprising resources here for commonality between men and women if we acknowledge and understand the intimate relationship between language and physical life